Sky High [videorecording (DVD)] - Giacchino, Michael (Disney DVD., 2005)
When you're the son of the world's most legendary superheroes there's only one school for you--Sky High, an elite high school that molds today's power-gifted students into tomorrow's superheroes. The problem is that Will Stronghold has no superpowers!